Effects of clinical local factors on thickness and morphology of Schneiderian membrane: A retrospective clinical study - Ramanauskaite, Ausra; Ataman-Duruel, Emel T.; Duruel, Onurcem; Tozum, Melek D.; Yildirim, Tuba T.; Tozum, Tolga F. (Wiley, 2019)
Background It was informed that the thickness of maxillary sinus membrane may be affected by the local and patient-related factors in the literature. Purpose The aim of this retrospective study is to evaluate factors that may have an influence of the thickness and morphology of the maxillary sinus membrane. Materials and Methods A total of 414 cone beam computed tomography images of 207 patients were evaluated. Radiographic parameters were evaluated at each maxillary premolar and molar tooth regions. Statistical analysis was performed to assess the association between the maxillary sinus mucosa thickness and morphology. The following factors including gender, periodontal bone loss (PBL), bone density, amount of residual alveolar bone at the edentulous space, vitality of the teeth present, and anatomical relationship between the sinus floor and posterior teeth were evaluated. Results The mean thickness of maxillary sinus membrane ranged between 1.47 to 2.92 mm and was significantly thicker in male subjects (P < .05). Positive correlation was detected between the sinus membrane thickness values in each posterior tooth region (P < .05). Thickening of the membrane was noted in 53% of the scans. The most commonly observed morphological change was flat thickening of the membrane (21%). No correlation was found between the evaluated local factors on the thickness and morphology of the maxillary sinus membrane (P > .05). Conclusions Tooth vitality, residual alveolar bone height, and PBL seem to have no effect on the thickness and morphology of the maxillary sinus membrane.
Keywords: CBCT imaging; computerized tomography; maxillary sinus; sinus floor elevation